Inhabiting a Time before Time. Freud’s Concept of Trauma as a Psychoanalytical Figure of Thought (Studia theodisca, 2019)
At present the term ‘trauma’ seems to be booming as a pattern of cultural interpretation. It connects discourses about medicine, psychoanalysis, art and literary theory, and social history. Today the ruptures and aporias of understanding, representation, communicability and referentiality are discussed in post-structuralist theories of meaning, but it was Freud who created for the first time a readable text about how the repetitious structure of trauma in its paradoxical temporality – the effect stands in as its cause – works as a missed experience at the interface of lives and texts.